2017
DOI: 10.1371/journal.pone.0172684
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive growth performance, immune function, plasma biochemistry, gene expressions and cell death morphology responses to a daily corticosterone injection course in broiler chickens

Abstract: The massive meat production of broiler chickens make them continuously exposed to potential stressors that stimulate releasing of stress-related hormones like corticosterone (CORT) which is responsible for specific pathways in biological mechanisms and physiological activities. Therefore, this research was conducted to evaluate a wide range of responses related to broiler performance, immune function, plasma biochemistry, related gene expressions and cell death morphology during and after a 7-day course of COR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 85 publications
10
40
0
Order By: Relevance
“…Before reported the chronic heat stress-induced attenuation of the innate immune system 24 . In the present study, it had been observed changes in the biochemical parameters, HSPs, and pro- and anti-inflammatory cytokines in response to chronic heat stress and their effects on the immune system 40 . Heat stress affected the liver function and reduced bile acid content 41 .…”
Section: Discussionsupporting
confidence: 52%
“…Before reported the chronic heat stress-induced attenuation of the innate immune system 24 . In the present study, it had been observed changes in the biochemical parameters, HSPs, and pro- and anti-inflammatory cytokines in response to chronic heat stress and their effects on the immune system 40 . Heat stress affected the liver function and reduced bile acid content 41 .…”
Section: Discussionsupporting
confidence: 52%
“…The enzymolysis also had no effect on the relative weight of the spleen. This may be due to the fact that major immunological activities are concentrated in the organs that produce the most antibodies (B and T cells) (Mehaisen et al, 2017). In addition, the relative weights of the pancreas and liver did not show changes due to the experimental diets (Table 3).…”
Section: Discussionmentioning
confidence: 95%
“…Physiological indicators, such as the heterophil to lymphocyte (H/L) ratio and corticosterone concentration in blood serum, can also provide welfare information. Heterophils tend to increase and lymphocytes decrease in response to stress, but this avian immune response takes some time, measured in hours to days, to initiate, while a corticosterone response usually occurs within minutes [13][14][15][16]. Physical indicators, such as the weight of lymphoid organs, are related to stressor response through immune activation and suppression [17].…”
Section: Introductionmentioning
confidence: 99%